Silver-decorated nanobeads for high-performance and flexible analysis of Shigella dysenteriae utilizing a paper-based aptasensor - Jampasa, Sakda; Sangthong, Natthawut; Ozer, Tugba; Traipop, Surinya; Ngamrojanavanich, Nattaya; Panphut, Wattana; Chailapakul, Orawon; Kaneta, Takashi; Wonsawat, Wanida (ELSEVIER SCIENCE SA, 2026)
Shigella dysenteriae (S. dysenteriae) is a significant pathogen associated with foodborne diseases, yet it is often overlooked, posing a risk of widespread outbreaks. Traditional detection methods rely on complex and lengthy cell culture techniques. In response, we have developed a cost-effective, portable, and versatile paper-based aptasensor that utilizes silver-decorated magnetic nanobeads (Ag/MBs) for S. dysenteriae detection. This aptasensor was designed to enable voltammetric and impedance analyses, offering rapid screening and sensitive detection of S. dysenteriae in food samples. Ag is chemically decorated on carboxyl-functionalized MBs, with aptamer probes attached. The current response from Ag indicated the presence of the pathogen, while bacterial binding reduced the Ag signal due to insulating properties, measured via differential pulse voltammetry (DPV). Concurrently, the formation of immunocomplexes increased charge transfer resistance, facilitating electrochemical impedance spectroscopy (EIS) measurement within a single device and lowering the detection limit. MB-based assays helped concentrate S. dysenteriae, thus achieving broad linearity (DPV = 102-108 CFU/mL, EIS = 101-109 CFU/mL) and high sensitivity (DPV = 90 CFU/mL, EIS = 8.09 CFU/mL) while maintaining specificity. The aptasensor also integrated near-field communication technology for convenient on-site analyses, making it an effective, sensitive, yet portable platform for detecting S. dysenteriae and other microorganisms.
Keywords: S. dysenteriae; Label-free format; Electrochemical paper-based aptasensor; Silver-decorated nanobeads; Near-field communication; SURFACES; SENSOR; TOXIN; ASSAY; Biochemistry & Molecular Biology; Life Sciences & Biomedicine - Other Topics; Biophysics; Electrochemistry